Yield and nutritive value of maize (Zea mays L.) forage as affected by plant density, sowing date and age at harvest - Salama, Heba Sabry Attia (Italian Journal of Agronomy, 2019)
The current study was carried out in Alexandria, Egypt and investigated the effect of sowing date; 1st May, 1st July, and 1st September 2017 and 2018, and age at harvest; 45, 55 and 65 days after sowing (DAS) on yield and quality of maize green forage grown with three plant densities (120, 160, and 200 kg ha–1). Sowing at 1st of May produced the highest significant amount of fresh yield (41.51 t ha–1 in average). Sowing at 1st of July resulted in the production of significantly lower yield (24.54 t ha–1 in average), however, higher dry matter content (175.99 g kg–1 in average), compared to sowing at 1st of May (143.62 g kg–1 in average). A pronounced increase in fresh yield was observed when maize was harvested at 55 DAS (30.89 t ha–1 in average) compared to harvesting at 45 DAS (22.92 t ha–1 in average). Meanwhile, the increase in fresh yield from 55 DAS to 65 DAS was non-significant. The effect of sowing date on quality parameters was greatly dependent on the age of plant at harvest. Harvesting maize green forage at 65 DAS, reflecting an advanced stage of maturity, caused a significant reduction in the crude protein (CP), and a significant increase in the neutral and acid detergent fibre fractions (NDF and ADF), resulting in a decline in the digestible organic matter (DOM). Plant density exerted non-significant influence on the fresh yield and DM content, minimal effect on the CP content, while the effect on the NDF and ADF contents was dependent on the age at harvest. The lignin content (ADL) of the herbage significantly decreased with increasing the plant density. Variations in the DOM were most dependent on the variations in CP content, followed by the variations in ADF and ADL contents. In conclusion, it is recommended to grow green forage maize twice a season on the 1st of May and 1st of July, with intermediate plant density (160 kg ha–1), and harvest it not later than 55 DAS to achieve the optimum balance between herbage productivity and nutritive value.